PERTEMUAN 2+2 INDONESIA-AUSTRALIA 2023 SEBAGAI RESPON ATAS RIVALITAS AS-TIONGKOK DI KAWASAN ASIA PASIFIK - Zherlindya Putri Darmawan, Arthamevya; Abdurrohim, Muhammad (Prodi Ilmu Hubungan Internasional, Universitas Fajar, 2023)
This research aims to examine how Australia's domestic political turmoil produces foreign policy related to regional dynamics through the 2+2 meeting with Indonesia in 2023. The threat of AUKUS nuclear-powered submarines as a form of US and Chinese rivalry in the region attracted international attention. The US together with AUKUS tried to match China's strength in the Asia Pacific region. The following year Australia held a meeting with Indonesia to discuss regional dynamics. This research uses descriptive qualitative methodology based on social phenomena in the form of descriptive explanations. This research uses the Adaptive Model Foreign Policy Theory which argues that external and internal changes will affect Foreign Policy to adapt to these changes. In this study, researchers found that in addition to international pressure, there was political turmoil that caused Australia to change its foreign policy orientation, through defense cooperation with Indonesia.